2014
DOI: 10.1332/204080514x13922138865396
|View full text |Cite
|
Sign up to set email alerts
|

Governance systems of grant-making foundations

Abstract: This article aims at filling an important gap in governance literature. Most governance studies are board-focused and hardly differentiate between different types of non-profit organisations. Surveys on governance structures of independent grant-making foundations are almost non-existent in the current literature. Due to the heavy focus on boards, the roles of executive directors in governance are somewhat neglected. This article presents the results of a multiple case study research project with 12 grant-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…The traceability of results through written documentation and standardised processes is necessary to build a constant and reliable working environment. Especially for foundation boards, access to information is important as they usually are not involved in the daily foundation's activities (Bethmann, 2019). However, transparency is a means to an end, and the extent and content of the information shared should be suited to the purpose (Mayrhofer & Meyer, 2020).…”
Section: Governance: Principles and Modelsmentioning
confidence: 99%
“…The traceability of results through written documentation and standardised processes is necessary to build a constant and reliable working environment. Especially for foundation boards, access to information is important as they usually are not involved in the daily foundation's activities (Bethmann, 2019). However, transparency is a means to an end, and the extent and content of the information shared should be suited to the purpose (Mayrhofer & Meyer, 2020).…”
Section: Governance: Principles and Modelsmentioning
confidence: 99%
“…Indeed, foundation boards are often comprised of senior executives (or the CEO) of the company (Renz et al, 2020), which implies that corporate leadership is strongly connected to the governance of the corporate foundation. Previous research has shown that business interests significantly impact the nature of the relationship between a company and its corporate foundation, which, in turn, impacts the foundation's governance structure, the direction of operations, and organizational outcomes (Bethmann & Von Schnurbein, 2015; Pedrini & Minciullo, 2011).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…However, corporate foundations may encounter challenges in acting independently when they are not able to employ their own staff. Employees seconded or reassigned from the corporation often have limited professional charitable experience and knowledge of nonprofit management (Bethmann & Von Schnurbein, 2015; Westhues & Einwiller, 2006). It may also be the case that CEOs or corporate employees working at the firm's foundation might experience a blurring of identity and allegiance to the foundation (Renz et al, 2020).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two members mentioned impact measurement (e.g., Bekkers & Verkaik, 2015;Von Schnurbein, 2016). Foundation governance was also mentioned twice (e.g., Bethmann, Von Schnurbein & Studer, 2014). Endowment management, grantmaking, fiscal sponsorship, relations between staff and boards were all mentioned once (e.g., Lideikyte Huber & Peter, 2020).…”
Section: A Research Agendamentioning
confidence: 99%